2018
DOI: 10.3329/jninb.v4i2.38920
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging-Based Evaluation of the Etiology of Non-Traumatic Myelopathies in Bangladesh: A Hospital-based Observational Cross-sectional Study from Two Tertiary Care Centers of Dhaka

Abstract: Background: Non-traumatic myelopathies has several etiologies. Objectives: The aim of the study was to see the etiology of non-traumatic myelopathy based on magnetic resonance imaging (MRI) changes in the context of Bangladesh. Methodology: Patients clinically diagnosed as non-traumatic myelopathy in the department of neurology of Sir Salimullah Medical College and Hospital (SSMCH), and in the inpatient wards of the National Institute of Neurosciences (NINS), considering the inclusion and exclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…Similar results were found by the investigators of the study conducted in Bangladesh where investigators found among etiologies that cervical spondylotic myelopathy (31%) was most commonly diagnosed [25]. The cervical myelopathy syndrome was first described in 1952, in some cases performed by Brain and colleagues [26].…”
Section: Original Research Articlesupporting
confidence: 83%
See 2 more Smart Citations
“…Similar results were found by the investigators of the study conducted in Bangladesh where investigators found among etiologies that cervical spondylotic myelopathy (31%) was most commonly diagnosed [25]. The cervical myelopathy syndrome was first described in 1952, in some cases performed by Brain and colleagues [26].…”
Section: Original Research Articlesupporting
confidence: 83%
“…The present study included the majority of participants in between the age group of 51-60 years and showed a predominance of the male population. A study conducted in Bangladesh on patients with non-traumatic myelopathy also included the highest number of patients (26.0%) in the age group 51-60 years [14]. The age group of patients of a retrospective study conducted in Tikur Anbessa Hospital did not match with our participants as the majority were between the age group of 16-30 years of age but their data also showed male predominance [15].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation